Trendwatching-Driven Modelling and Management of Structural Labour Market Imbalances - Herasymenko, Yuliia; Komelina, Olha; Hrybovska, Yuliia; Pakhomov, Ilya (Dr. Viktor Koval, 2025)
Introduction. In the context of the crisis of the Ukrainian economy, which was significantly exacerbated by labour market imbalances, institutional structures and businesses need to promptly identify asymmetries of labour market factors and relevant results of trendwatching of the market situation. Simultaneously, trendwatching is significantly complicated by uncertainty and sharp changes in the main indicators of demand and supply in the Ukrainian labour market. This necessitates the development of a new mathematical model of trendwatching that is suitable for use in the specifics of the labour market and its application in forecasting the indicators of the specified market. Aim and tasks. This study aims to develop new mathematical tools for trendwatching, adapted to the conditions of Ukraine, and their use for assessing and forecasting labour market indicators.  Results. Forecasting the impact of the main factors on the labour market of Ukraine, contributing to the increase in wages in the IT industry, using the developed mathematical model, indicated that the impact of uncertainty is significant, from 5% to 20%. The differences in the average monthly wage by industry tend to grow, and the forecast data for 2025 will be 1.53 times greater than the indicator for 2021. This indicates that not only the magnitude (by two or more times) but also the directions of the demand-supply vectors change per quarter, even in critical infrastructure sectors. Simultaneously, a significant loss of high-quality human resources is indicated due to the outflow of highly qualified workers abroad. Conclusions. The labour market trendwatching indicated that the difference in the rate of change in the number of resumes in the period 2023-2024 is 12.79 times greater than the rate of change in the number of vacancies, with a concomitant low level of convergence of the nonlinear trends of the specified indicators, which is evidence of a significant gap in the demand and supply of employee competencies. This is confirmed by a significant (1.5 times higher than the EU) unemployment rate among people with higher education levels. A significant slope ratio of the linear trend of the ratio of the standard deviation of the average monthly salary by industry to its average value in the economy (4.382) confirms the trend of increasing discrepancies in the personnel shortage by industry and the post-war period. Simultaneously, a trend towards an increase in job offers with increasing wages was detected, indicating a tendency in Ukraine to abandon the policy of cheap labour.